PENGARUH KEPUASAN KERJA TERHADAP LOYALITAS KARYAWAN (STUDI KASUS PADA PT. VERITRA SENTOSA INTERNASIONAL) - Aminudin Aminudin; Arief Tasrif (Scientia Regendi, 2020)
Employee loyalty is very important for the company, as the employee with high loyalty tend to do good performance and always willing to maintain and defend the company. Based on observations, there are indications that the employee loyalty of PT Veritra Sentosa Internasional is decreasing as seen from the high level of employee turnover which is influenced by placements that are not in accordance with their competencies and it is also affected by lack of job satisfaction. Based on this background, this study aims to find out and examine job satisfaction and its effect on employee loyalty. The method used in this study is a quantitative method with data analysis techniques using multiple linear regression. The data used are primary data which is collected through questionnaires. The samples used in this study were 136 employees of PT Veritra Sentosa Internasional. The results showed that job satisfaction affect employee loyalty. Furthermore, competence, placement and job satisfaction all together affect employee loyalty simultaneously. Based on the regression analysis it is found out that the regression coefficient is positive, so it can be concluded that the better of job satisfaction, the higher the employee loyalty will be.